2016
DOI: 10.5851/kosfa.2016.36.6.729
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Physicochemical and Sensory Properties of Fermented Sausage from Sulfur-fed Pork

Abstract: This study was performed to evaluate the quality of fermented sausages manufactured with processed sulfur-fed pigs. The fermented sausages were divided into two groups; one was manufactured with non sulfur-fed pigs (NP), the other one was made with processed sulfur-fed pigs (SP). No differences were found in moisture and fat contents (p>0.05) between NP and SP, but the protein and ash contents of SP were significantly higher than those of NP (p<0.05). The pH of SP was significantly lower than that of NP, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…Seong et al ( 2016 ) also determined that the pH values of fermented sausages produced with soy protein decreased to 5.0–5.1. Ju et al ( 2016 ) reported a decrease in pH values of fermented pork sausages up to 21 d fermentation. This pH change has been linked to the microbial activity of LAB, which metabolizes sugar in meat to produce lactic acid (Ju et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seong et al ( 2016 ) also determined that the pH values of fermented sausages produced with soy protein decreased to 5.0–5.1. Ju et al ( 2016 ) reported a decrease in pH values of fermented pork sausages up to 21 d fermentation. This pH change has been linked to the microbial activity of LAB, which metabolizes sugar in meat to produce lactic acid (Ju et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ju et al ( 2016 ) reported a decrease in pH values of fermented pork sausages up to 21 d fermentation. This pH change has been linked to the microbial activity of LAB, which metabolizes sugar in meat to produce lactic acid (Ju et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, dry-cured meat products derived from 3 g kg −1 SFPs showed extended shelf life and sensory quality. 8 Furthermore, the amount of free amino acids in dry-cured meat derived from pigs exposed to diets supplemented with processed sulfur was relatively high compared with meat derived from pigs fed a basal diet. 9 However, only limited information is available regarding the taste components of raw pork obtained from SFPs during aging.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in oxidative stability and meat quality of pork was demonstrated by Lee et al ., who reported a high oxidative stability in pigs fed 300 and 500 ppm organic sulfur methyl sulfonyl methane. Additionally, dry‐cured meat products derived from 3 g kg −1 SFPs showed extended shelf life and sensory quality . Furthermore, the amount of free amino acids in dry‐cured meat derived from pigs exposed to diets supplemented with processed sulfur was relatively high compared with meat derived from pigs fed a basal diet .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on meat have usually attempted to enhance the quality of meat employing many different methods (Ju et al, 2016). Reducing lipid oxidation is a key route to improve meat quality.…”
Section: Introductionmentioning
confidence: 99%